2006
DOI: 10.2174/138161206778343118
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 5 Inhibitors - Drug Design and Differentiation Based on Selectivity, Pharmacokinetic and Efficacy Profiles

Abstract: The discovery that inhibition of phosphodiesterase-5 (PDE5) reduces the degradation of cGMP, allowing erectile function to occur by relaxation of penile smooth muscle, represents a revolutionary approach or the treatment of erectile dysfunction (ED). Three PDE5 inhibitors (sildenafil, tadalafil, and vardenafil) are clinically available at this time, and extensive drug design efforts are registered for finding agents with a better activity, enhanced selectivity and reduced side effects. Many classes of such com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 30 publications
(103 reference statements)
2
35
0
Order By: Relevance
“…However it was reported in a recent study that * mean p < 0.05 the duration of action of sildenafil and vardenafil is about 4 hours, whereas Tadalafil action is approximately 36 hours, and the overall safety of the treatment is good (23). In another study by Doggrell S (24) it was concluded that Tadalafil is similarly effective as Sildenafil in the treatment of ED and in comparison studies; Tadalafil is preferred to Sildenafil (50/100mg) by men with ED, possibly because of its longer duration of action.…”
Section: -Penile Circumference At Maximum Erection (Cm)mentioning
confidence: 88%
“…However it was reported in a recent study that * mean p < 0.05 the duration of action of sildenafil and vardenafil is about 4 hours, whereas Tadalafil action is approximately 36 hours, and the overall safety of the treatment is good (23). In another study by Doggrell S (24) it was concluded that Tadalafil is similarly effective as Sildenafil in the treatment of ED and in comparison studies; Tadalafil is preferred to Sildenafil (50/100mg) by men with ED, possibly because of its longer duration of action.…”
Section: -Penile Circumference At Maximum Erection (Cm)mentioning
confidence: 88%
“…Although having selective inhibitory effects on PDE5 activity, sildenafil and vardenafil differ from tadalafil in their interaction with the catalytic domain of PDE5, which forms the basis of their difference in affinity and effectiveness (25). Moreover, unlike sildenafil and vardenafil with 4 h biological half-life, tadalafil is a long-acting PDE5A inhibitor with 17.5 h biological half-life.…”
Section: Discussionmentioning
confidence: 99%
“…PDE5i are also used in the treatment of pulmonary hypertension (Supuran et al, 2006;Aversa et al, 2006).These drugs act selectively in the smooth muscle of the lungs and penis because their receptors are primarily distributed within these areas (Oka et al, 2015). PDE5i are so called because they selectively inhibit the action of phosphodiesterase type 5, an enzyme which promotes the degradation of cyclic guanosine monophosphate (cGMP) (Salam et al, 2015).Thus, erection is prolonged as long ascGMP is not degraded.…”
Section: Introductionmentioning
confidence: 99%